Stress Associated with Transportation: A Survey of Persons with Visual Impairments. (May 2017) - Crudden, Adele; Cmar, Jennifer L.; McDonnall, Michele C.
Introduction: This study evaluated transportation-related stress and factors predicting stress among persons with visual impairments. Methods: Participants with visual impairments completed electronic surveys rating their stress levels experienced when completing various walking and public transportation tasks. They also indicated activities they avoided due to transportation stress. Results: Higher stress was reported for navigating unfamiliar bus routes, walking in urban areas without sidewalks, and walking in unfamiliar places. Significant predictors of walking stress were age, years since vision loss, dog guide use, physical limitations, and frequency of public transportation use. Significant predictors of public transportation stress were age, orientation and mobility (O&M) training, physical limitations, and frequency of public transportation use. Most-avoided activities due to transportation-related stress were entertainment or leisure activities and visiting family and friends. Discussion: Unfamiliar situations and unpredictable environments were associated with higher stress. Frequent public transportation use and longer time since vision loss predicted lower stress, which indicates that increased and varied experiences may affect transportation-related stress. Older persons and persons with physical limitations had more transportation-related stress. Social activities, which are important in managing stress, were most frequently avoided due to transportation stress. Implications for practitioners: O&M instructors should keep in mind that providing varied experiences and longer training is indicated for persons with high stress, particularly for older persons, and those with recent vision loss or physical limitations. Everyone involved in the rehabilitation process should remember that building relationships with consumers, encouraging public transportation use, participating in support groups, and overcoming travel barriers for social activities may help reduce transportation stress.